The American YMCA and Revolutionary Russia - Mott, John R. (John Raleigh), 1865-1955 (Book collections on Project MUSE., 2020)
"A collection of public addresses and letters concerning John R. Mott's participation in the US Root Mission to Russia in 1917."--